Taco complex derived from a bis-crown ether capable of executing molecular logic operation through reversible complexation - Mandal, Amal Kumar; Das, Priyadip; Mahato, Prasenjit; Acharya, Suhash; Das, Amitava (Journal of Organic Chemistry, 2012)
As learned from natural systems, self-assembly and self-sorting help in interconnecting different molecular logic gates and thus achieve high-level logic functions. In this context, demonstration of important logic operations using changes in optical responses due to the formation of molecular assemblies is even more desirable for the construction of a molecular computer. Synthesis of an appropriate divalent as well as a luminescent crown ether based host 1 and paraquat derivatives, 2(PF6)2 and 3(PF6)2, as guests helped in demonstrating a reversible [3](taco complex) (1·{2(PF6)2}2 or 1·{3(PF6)2}2) formation in nonpolar solvent. Detailed 1H NMR studies revealed that two paraquat units were bound cooperatively by the two crown units in 1. Because of preorganization, the flexible host molecule 1 adopts a folded conformation, where each of two paraquat units remain sandwiched between the two aromatic units of each folded crown ether moiety in 1. Disassembly of the “taco” complex in the presence of KPF6 and reassembly on subsequent addition of DB18C6 was initially demonstrated by 1H NMR spectral studies, which were subsequently corroborated through luminescence spectral studies. Further, luminescence spectral responses as output signals with appropriate and two independent molecular inputs could be correlated to demonstrate basic logic operation like OR and YES gates, while the results of the three molecular inputs could be utilized to demonstrate important logic operation like an INHIBIT gate.